Opportunities, Challenges, and Scientific Progress in Hemp Crops - Kacper Piotr Kaminski; Julia Hoeng; Fernando Goffman; Walter K. Schlage; Diogo Latino (Molecules, 2024)
The resurgence of cannabis (Cannabis sativa L.) has been propelled by changes in the legal framework governing its cultivation and use, increased demand for hemp-derived products, and studies recognizing the industrial and health benefits of hemp. This has led to the creation of novel high-cannabidiol, low-Δ9-tetrahydrocannabinol varieties, enabling hemp crop expansion worldwide. This review elucidates the recent implications for hemp cultivation in Europe, with a focus on the legislative impacts on the cultivation practices, prospective breeding efforts, and dynamic scientific landscape surrounding this crop. We also review the current cultivars’ cannabinoid composition of the European hemp market and its major differences with that of the United States.